If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(6 + 9) = -6 Combine like terms: 6 + 9 = 15 -3(15) = -6 Multiply -3 * 15 -45 = -6 Solving -45 = -6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2x^2-9x-1=-8x | | (x+6)-x= | | -y=12-0 | | 4x+43=10x+55 | | 4n+8=9n-9 | | 60+5w=8w+45 | | 62-6x=32 | | 4x+43=-10x-55 | | 5(4+n)=30 | | 2x^2-4x-2=-1 | | 4sec^2x=8 | | a+a+a+a=-22 | | 4w=10-w | | 4x^2+3=6x+1 | | -x-21=2x+9 | | x^3+11x^2-20x-300=0 | | 12-4a=-7a+4(-2a-8) | | 23*15=25 | | 3v^2+36v+49-8v=0 | | x-6=24-4x | | 3x^2+x+4=8x | | 6x+4=32-3x | | 3y=5-x | | 1/3(x+12)=12 | | 4(1-2u)=2(u+2) | | 2y=6y-11 | | 6x-4=32-3x | | 43X=8X+1 | | -5x^4+20x^3+60x^2=0 | | 40+3r=-7r+4(8r-1) | | p/1.52=-3,600 | | 2x^2+22x+12=9x+6 |